Antibacterial activity of microwave synthesized hydroxyapatite against cariogenic bacteria: A preliminary study - Ahmad Zharif Ibrahim; Alaa Sabah Hussein; Hasnah Begum Said Gulam Khan; Norzalina Ghazali (Elsevier, 2024)
Introduction: The effects of hydroxyapatite (HA) on oral bacteria and biofilm remains inconclusive, with conflicting results. Studies assessing its effect against caries-causing bacteria are limited. Objective: This study aimed to explore the antibacterial activity of HA synthesized using microwave against two of the most common cariogenic bacteria, Streptococcus mutans (S. mutans) and Streptococcus sobrinus (S. sobrinus). Methods: HA was chemically synthesized using a microwave. To verify the existence of the crystalline phase and the calcium and phosphate content, X-ray diffraction (XRD) and energy-dispersive X-ray (EDX) analysis were employed, respectively. Reduction in bacterial growth was used to assess the antibacterial effects of 10 %, 20 %, and 30 % HA against the tested bacteria. Results: The presence of the hydroxyapatite crystallite phase was verified using XRD, while EDX revealed the Calcium to Phosphorus (Ca/P) ratio to be 1.6. In response to the 10 %, 20 %, and 30 % HA, S. mutans were reduced by 14.5 %, 15.6 %, and 23.4 %, whereas S. sobrinus decreased by 17.1 %, 60.8 %, and 98.6 %, respectively. Conclusion: Microwave-synthesized HA could have antibacterial properties against caries-causing bacteria with different potencies depending on concentration and bacteria.